Sosialisasi Peraturan Daerah Provinsi DKI Jakarta Tentang Kependidikan - Deni Nasir Ahmad; Sumiah Nasution; Rahmatulloh Rahmatulloh; Mamik Suendarti; Napis Napis (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2024)
The aim of community service activities is to help the community facilitate the provision of information related to education in the DKI Jakarta provincial government. The methods used in this activity are: a. Direct observation means that the service member comes directly to the service location to collect data. b. Carrying out community service activities by conducting outreach and training to community service partners. c. Carrying out evaluations and sharing together to produce final results of activities. The results of the community service activities that have been carried out are that the community from the community service partners provide feedback to us, the service team, namely input that supports the continuation of community service activities. The conclusions from the community service activities as follows: educational outreach activities in the DKI Jakarta provincial government were very well received by the participants with many giving suggestions for additional scholarships for outstanding students and other learning assistance